Mineralogy and genetic features of the Cu-As-Ni-Sb-Pb mineralization from the Mlakva polymetallic deposit (Serbia) — New occurrence of (Ni-Sb)-bearing Cu-arsenides - Radosavljević-Mihajlović, Ana S.; Stojanović, Jovica N.; Radosavljević, Slobodan A.; Pačevski, Aleksandar M.; Vuković, Nikola S.; Tošović, Radule D. (Ore geology reviews, 2017)
(Ni-Sb)-bearing Cu-arsenides are rare minerals within the Mlakva and Kram mining sectors (Boranja ore field) one of the less-known Serbian Cu deposits. (Ni-Sb)-bearing Cu-arsenides were collected from the Mlakva skarn-replacement Cu(Ag,Bi)-FeS polymetallic deposit. The identified phases include β-domeykite, Ni-bearing koutekite and (Ni-Sb)-bearing α-domeykite. (Ni-Sb)-bearing Cu-arsenides are associated with nickeline, arsenical breithauptite, chalcocite, native Ag, native Pb and litharge. Pyrrhotite, pyrite, chalcopyrite, cubanite, bismuthinite, molybdenite, sphalerite, galena, Pb(Cu)-Bi sulfosalts and native Bi, as well as minor magnetite, scheelite and powellite are associated with the sulfide paragenesis. The electron microprobe analyses of the (Ni-Sb)-bearing Cu-arsenides yielded the following average formulae: (Cu2.73,Ni0.17,Fe0.03,Ag0.01)∑2.94(As0.98,Sb0.05,S0.02)∑1.06–β-domeykite (simplified formula (Cu2.7,Ni0.2)∑2.9As1.1); (Cu3.40,Ni1.40,Fe0.11)∑4.91(As1.94,Sb0.13,S0.02)∑2.08–Ni-bearing koutekite (simplified formula (Cu3.4Ni1.5)∑4.9As2.1); and Cu1.97(Ni0.98,Fe0.03)∑1.01(As0.81,Sb0.22)∑1.03–(Ni–Sb)-bearing α-domeykite (simplified formula Cu2NiAs). The Rietveld refinement yielded the following unit-cell parameters for β-domeykite and Ni–bearing koutekite: a=7.1331(4); c=7.3042(5) Å; V=321.86(2) Å3, and a=5.922(4); b=11.447(9); c=5.480(4) Å; V=371.48(5) Å3, respectively. Ore geology, paragenetic assemblages and genesis of the Mlakva deposit are discussed in detail and the Cu-As-Ni-Sb-Pb mineralization has been compared with similar well-known global deposits. [Display omitted] •(Ni-Sb)-bearing copper-arsenides•Skarn-replacement Cu(Ag,Bi)-FeS polymetallic deposits•Massive and stockwork/disseminated ores•Boranja ore field, Podrinje metallogenic district, Serbia